A method for producing a multifunctional activated carbon catalyst

Multifunctional honeycomb activated carbon catalyst was prepared through hydrothermal slurrying method and multi-step molding process, which solved the problems of complex processes and environmental pollution in the prior art, and achieved simplification of the production process and efficient performance of the catalyst.

CN116212872BActive Publication Date: 2025-02-14FUJIAN NANPING SANYUAN CYCLE TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202211736098.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-31
Publication Date
2025-02-14
Estimated Expiration
2042-12-31

AI Technical Summary

Technical Problem

The existing preparation methods of activated carbon support catalysts have problems such as complex process, long production time, low practicality, high production costs and large environmental pollution, making it difficult to achieve industrial scale production.

Method used

The activated carbon powder, inorganic binder and metal oxide are mixed in a certain proportion by hydrothermal slurrying method, and multifunctional honeycombs are prepared by high-pressure dehydration, coarse refining, refining, mold forming, heating and drying and activation. activated carbon catalyst.

Benefits of technology

The production process has been simplified, the production cost and environmentally friendly treatment cost are reduced, and the emission of VOC and nitrogen oxides after organic matter decomposition is avoided. The prepared catalyst has high strength, good catalytic properties and resistance to low concentration acid and alkali, high humidity, etc. Characteristics of working conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116212872B_ABST
    Figure CN116212872B_ABST
Patent Text Reader

Abstract

The present invention discloses a production method of a multifunctional activated carbon catalyst, comprising: adding activated carbon powder, inorganic binder, and active component into a reaction tank in proportion for hydrothermal reaction, and adjusting pH with dilute phosphoric acid during the reaction; pumping the mixed slurry to a dehydrator, dehydrating after the feed is full, and unloading after dehydration to obtain a mixed mud material; kneading the mixed mud material, and conveying the discharged material to a cylindrical extruder for extrusion molding to obtain a crude columnar mud material; conveying the crude columnar mud material to a vacuum cylindrical extruder for extrusion molding to obtain a refined columnar mud material; conveying the refined columnar mud material to an extruder equipped with a honeycomb mold for extrusion molding and cutting, and gradually drying the honeycomb molded wet material to obtain a honeycomb dry material; the honeycomb dry material is put into a sealed oxygen-deficient high-temperature furnace for activation, and a honeycomb activated carbon catalyst is obtained after cooling. The production method provided by the present invention has no VOC emissions, and the produced activated carbon catalyst has good strength and catalytic performance, and is suitable for promotion and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of activated carbon catalyst production, and specifically relates to a production method of a multifunctional activated carbon catalyst. Background Art

[0002] Activated carbon-supported catalysts are widely used in gas-phase and liquid-phase catalysis, such as: ① Flue gas treatment, such as desulfurization, SCR denitrification, mercury removal, CO removal; ② Preparation of high-purity fuel gas, such as catalytic decomposition of ammonia to produce hydrogen, CO2 electrocatalytic reduction (CO2RR) to produce CO; ③ Organic synthesis, such as catalytic oxidation of styrene to produce benzaldehyde, C-C homogeneous coupling reaction, catalytic reaction of specific functional groups such as hydroxyl, carboxyl, carbonyl, aldehyde, condensation of specific chemical bonds, polymerization reaction, etc.; ④ Fuel cells, such as oxygen reduction reaction ( ORR) catalyst; ⑤ Wastewater treatment, such as multiphase Fenton catalysis, composite photocatalysis, heterogeneous catalytic wet oxidation CWAO and electrochemical catalysis and other wastewater catalytic treatment; ⑥ Petrochemical industry, such as oil desulfurization, deodorization, loading of Mo, Co, Ni, W, Fe, Cu, Mn, Si, K and other metals for catalytic crude oil hydrogenation, Fischer-Tropsch synthesis, crude oil refining, oil hydrogenation, direct liquefaction of coal and indirect liquefaction of oil products, etc.; ⑦ Silica gel industry; ⑧ Food and medicine; ⑨ Military industry and high technology, etc. At present, the commonly used methods for preparing activated carbon carrier catalysts are: direct addition method, chemical activation method, impregnation loading method, and co-thermal infiltration method. All four methods have certain limitations. Most of the existing technologies use the impregnation loading method, and simplifying the production process, reducing production costs, reducing environmental protection treatment costs, and environmental pollution are the mainstream directions of current technological development.

[0003] The existing technology has the disadvantages of complex production process, long process time, low production practicality, low production cost and high environmental pollution, which makes it difficult to achieve industrial scale production. For example, the application number is CN202011478703.7, a mesoporous manganese-based composite oxide and its preparation method and application, and CN202011326049.8, a high-efficiency moisture-resistant ozone decomposition catalyst and its preparation method and application, using the impregnation loading method, CN202010982855.4, an ozone oxidation catalyst, preparation method and ozone catalytic oxidation device, CN201911301188.2, a metal-supported catalyst preparation method for moderate catalytic ozonation to remove ammonia nitrogen from water, these invention technologies have complex loading processes, and after adding a large amount of organic matter to decompose, there are nitrogen oxides, VOCs and other pollution in the tail gas, which are difficult to handle and have poor practicality. Summary of the invention

[0004] The present invention provides a method for producing a multifunctional activated carbon catalyst to solve the above problems.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0006] A method for producing a multifunctional activated carbon catalyst comprises the following steps:

[0007] 1) Hydrothermal slurry preparation:

[0008] The activated carbon powder, the inorganic binder and the active component are put into a stirring reaction tank equipped with hot water in a mass ratio of 1:0.5 to 1:0 to 0.5 for hydrothermal reaction, and the pH is adjusted to 5 to 7 with dilute phosphoric acid during the hydrothermal reaction to obtain a mixed slurry;

[0009] 2) High pressure dehydration:

[0010] The mixed slurry in step 1) is pumped to a dehydrator, and after the feed is full, it is dehydrated, and the material is unloaded after dehydration to obtain a mixed slurry with a filter cake moisture content of less than 55%;

[0011] 3) Rough refining and molding:

[0012] The mixed clay material of step 2) is conveyed to a kneader for kneading, and the discharged material is conveyed to a cylindrical extruder for extrusion molding to obtain a crude columnar clay material;

[0013] 4) Refining and molding:

[0014] The crude columnar clay material of step 3) is conveyed by a conveyor belt to a vacuum cylindrical extruder for extrusion molding to obtain a refined columnar clay material;

[0015] 5) Mold forming:

[0016] The refined columnar mud material of step 4) is conveyed to an extruder equipped with a honeycomb mold for extrusion molding, and then automatically cut to obtain a honeycomb molding wet material;

[0017] 6) Heating and drying:

[0018] The honeycomb forming wet material of step 5) is gradually dried at a temperature range of 30 to 80° C. until the moisture content is less than 5%, thereby obtaining a honeycomb dry material;

[0019] 7) Activation:

[0020] The honeycomb dry material of step 6) is put into a sealed oxygen-deficient high-temperature furnace at 500-800° C. for activation, and a honeycomb activated carbon catalyst is obtained after cooling.

[0021] Preferably, in step 1), the activated carbon powder has a 200-mesh pass rate of more than 90% and a moisture content of less than 10%; the inorganic binder has a 200-mesh pass rate of more than 95% and a moisture content of less than 10%; and the active component has a 200-mesh pass rate of more than 95% and a moisture content of less than 10%.

[0022] Furthermore, the active component is a metal oxide, and the metal oxide is selected from one or more of manganese oxide, iron oxide, copper oxide, aluminum oxide, lanthanum oxide, cerium oxide, molybdenum oxide, and cobalt oxide; the inorganic binder is selected from one or more of attapulgite clay, kaolin, and sepiolite powder.

[0023] Preferably, in step 1), the temperature of the hot water is 30-100° C., the hydrothermal reaction time is 0.5-3 h, the solid content of the obtained mixed slurry is 15-30%, and the dilute phosphoric acid is 5-20% phosphoric acid.

[0024] Preferably, the dehydration in step 2) is carried out by high-pressure extrusion dehydration at 10 to 20 MPa.

[0025] Preferably, the filtered water obtained by dehydration in step 2) is recycled into a stirring tank for uniform slurry preparation.

[0026] Preferably, the kneading time of the mixed mud in step 3) is 30 to 60 minutes.

[0027] Preferably, the vacuum degree of the vacuum extraction in step 4) is -0.06 to -0.09 MPa.

[0028] Furthermore, in step 6), the mixture is gradually dried in a constant humidity environment at a temperature range of 30 to 80° C. to a moisture content of less than 5%, specifically:

[0029] The drying is carried out in three temperature ranges of 30-40°C, 40-50°C and 50-80°C in sequence until the moisture content is less than 5%, and the relative humidity of the constant humidity environment is controlled at 40-50%.

[0030] Preferably, the activation time in step 7) is 4 to 8 hours; the activated flue gas is passed through a heat exchanger to obtain hot air for heating and drying.

[0031] The present invention has the following advantages:

[0032] 1) The present invention uses activated carbon powder as raw material, and only uses a combination of activated carbon, inorganic binder, and metal oxide, without adding any organic components, and has no VOC emissions. The produced activated carbon catalyst has good strength and catalytic performance.

[0033] 2) The production process of the present invention is simple, the activation temperature is relatively low, the tail gas composition is simple and easy to recover waste heat and environmentally friendly treatment, thus achieving energy saving and consumption reduction, low production cost, and conducive to industrial promotion.

[0034] 3) The activated carbon catalyst produced by the present invention has the characteristics of high strength, high adsorption capacity, good catalytic effect, etc., making it suitable for catalytic adsorption and decomposition of VOC and COD in gas and liquid environments, catalytic decomposition of ozone, and resistance to low concentration acid and alkali, high humidity and other working conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0036] Figure 1 It is the process flow chart of the present invention. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Refer to the attached Figure 1 As shown, the present invention provides a method for producing a multifunctional activated carbon catalyst, comprising the following steps:

[0039] 1) Hydrothermal slurry preparation: select activated carbon powder with a 200-mesh pass rate of more than 90% and a moisture content of less than 10% as raw material, an inorganic binder with a 200-mesh pass rate of more than 95% and a moisture content of less than 10%, and a metal oxide with a 200-mesh pass rate of more than 95% and a moisture content of less than 10% as active components, and put the activated carbon powder, inorganic binder, and active component into a stirring reaction tank equipped with 30-100°C hot water in a mass ratio of 1:0.5-1:0-0.5 for hydrothermal reaction for 0.5-3h, and use 5-20% dilute phosphoric acid to adjust the pH to 5-7 during the hydrothermal reaction to obtain a mixed slurry with a solid content of 15-30%. During the thermal reaction, the addition of phosphoric acid can adjust the pH of the product, and the introduction of phosphate radicals to react with metal oxides and magnesium aluminum silicate in attapulgite to modify them, forming a self-adhesive structure of silicoaluminophosphate with stronger bonding strength, which can improve the strength and temperature resistance of the activated finished product, and form a molecular sieve-like structure to enhance the activity of the catalyst; at the same time, the hydrothermal reaction is used to enhance the reaction activity of the material in an aqueous environment, forming a gel reaction, forming a new surface structure and bonding force, and enhancing the reaction activity of the finished product.

[0040] The metal oxide is one or more of manganese oxide (YB / T 5084-2015 manganese dioxide ore powder for chemical industry), iron oxide (HG / T2574-2009 industrial iron oxide), copper oxide (HG / T 5354-2018 industrial active copper oxide), aluminum oxide (HG / T 3927-2020 industrial active aluminum oxide), lanthanum oxide (GB / T 4154-2006 lanthanum oxide), cerium oxide (GB / T 4155-2012 cerium oxide), molybdenum oxide (YB / T 5129-2012 molybdenum oxide), and cobalt oxide (YS / T 256-2009 cobalt oxide). The inorganic binder is one or more of attapulgite clay, kaolin, and sepiolite powder. Activated carbon powder can be selected according to the adsorption performance requirements to match the performance specifications of activated carbon (for example, the raw material adsorption index is iodine value 200 ~ 1800mg / g, specific surface area 600 ~ 2000m 2 / g, CTC adsorption value 30-80%, etc.).

[0041] 2) High-pressure dehydration: The mixed slurry in step 1) is pumped to the dehydrator through the feed pump. After the feed is full, it is dehydrated by high-pressure extrusion at 10-20 MPa. The filtered water is reused to enter the stirring tank for uniform slurry mixing. After dehydration, the material is unloaded to obtain a filter cake with a moisture content of less than 55%. The surface moisture is separated by high-pressure dehydration, and the filtered water is reused after dehydration. The filtered water contains soluble gel molecules, which can provide precursors for the next gel reaction.

[0042] 3) Rough refining and molding: The mixed mud material of step 2) is conveyed to a kneading machine via a conveyor belt and kneaded for 30 to 60 minutes, and the material is discharged from the conveyor belt and conveyed to a cylindrical extruder for extrusion molding to obtain a rough columnar mud material. 4) Refining and molding: The rough columnar mud material of step 3) is conveyed to a cylindrical extruder with a vacuum of -0.06 to -0.09 MPa via a conveyor belt for extrusion molding to obtain a refined columnar mud material. Vacuuming mud refining is beneficial to remove air from the material, making the material denser, and reducing the adverse effects of residual oxygen in the material on the catalyst, so that the strength and density of the molding material are higher.

[0043] 5) Mold forming: The refined columnar mud material of step 4) is conveyed by a belt to an extruder equipped with a honeycomb mold for extrusion forming, and then automatically cut to obtain a honeycomb molded wet material. The material obtained by honeycomb mold forming is in a honeycomb shape, which has a larger surface area than the granular shape, which is conducive to the catalytic reaction of the catalyst.

[0044] 6) Heating and drying: The honeycomb molding wet material of step 5) is placed in a drying room via a conveyor belt or manually, and is dried in a constant humidity environment of 40-50% at three temperature ranges of 30-40°C, 40-50°C, and 50-80°C in sequence. After drying, the moisture content is less than 5%, and a honeycomb dry material is obtained. During the drying process, in order to enhance the strength of the molding material and reduce breakage, the heating and drying adopts low-temperature slow drying, and the temperature and humidity of the drying are controlled to ensure uniform dehydration. Maintaining a constant humidity environment and slowly drying and dehydrating is beneficial to reducing cracks in the product.

[0045] 7) Activation: The honeycomb dry material of step 6) is put into a sealed oxygen-deficient high-temperature furnace at 500-800°C via a conveyor belt for activation. In order to enhance the reaction activity of the activated carbon catalyst, the high-temperature furnace uses high-temperature gas from the full combustion of natural gas for heating, replacing the traditional electric heating roasting, so that the material is heated more evenly, the carbon dioxide atmosphere is of high purity, the ablation of the activated carbon is reduced, and it is conducive to stabilizing the specific surface area and pore structure of the finished product. The activated flue gas is passed through a heat exchanger to obtain hot air for heating and drying, and the activation is carried out for 4-8 hours, and then the temperature is naturally reduced to obtain a honeycomb activated carbon catalyst. The activation time of the present invention is shorter, the activation temperature is lower, and energy saving and consumption reduction are reduced.

[0046] The process combination provided by the present invention can make the content of active components higher than that of the traditional impregnation method, and the adjustment range is wider, the combination of active components is more diversified, the application field is wider, and the catalyst performance can be accurately controlled.

[0047] Example 1

[0048] Select activated carbon powder with a 200 mesh pass rate of more than 90% and a moisture content of less than 10% (iodine value 1500m 2 / g) as raw materials, attapulgite clay and kaolin (attapulgite clay: kaolin = 1:1) with a 200 mesh pass rate of more than 95% and a moisture content of less than 10% as inorganic binders, copper oxide with a 200 mesh pass rate of more than 95% and a moisture content of less than 10% as active components, activated carbon powder, inorganic binder, and active components are put into a stirring reaction tank equipped with 65°C hot water according to a mass ratio of 1:0.5:0.2 for hydrothermal reaction for 2 hours, and 5-20% dilute phosphoric acid is used to adjust the pH to 5-7 during the hydrothermal reaction to obtain a mixed slurry with a solid content of 15-30%. The mixed slurry is pumped to a dehydrator through a feed pump, and after the feed is full, it is dehydrated by 10-20MPa high-pressure extrusion, and the filtered water is reused to enter the stirring tank for uniform slurrying, and the material is discharged after dehydration to obtain a mixed mud material with a filter cake moisture content of less than 55%.

[0049] The mixed mud is conveyed to the kneading machine via a conveyor belt and kneaded for 45 minutes. The material is conveyed to the conveyor belt and conveyed to the cylindrical extruder for extrusion molding to obtain a crude columnar mud. The crude columnar mud is conveyed to the cylindrical extruder with a vacuum of -0.06 to -0.09 MPa via a conveyor belt for extrusion molding to obtain a refined columnar mud; the refined columnar mud is conveyed by a belt to the extruder equipped with a honeycomb mold for extrusion molding, and then automatically cut to obtain a honeycomb molding wet material; the honeycomb molding wet material is placed in a drying room via a conveyor belt or manually, and is dried in three temperature sections of 30 to 40°C, 40 to 50°C, and 50 to 80°C in sequence. The moisture content after drying is less than 5%, and a honeycomb dry material is obtained.

[0050] The honeycomb dry material is put into a 650℃ sealed oxygen-deficient high-temperature furnace for activation via a conveyor belt. The high-temperature furnace uses high-temperature gas from the full combustion of natural gas for heating. The activated flue gas is passed through a heat exchanger to obtain hot air for heating and drying. It is activated for 4 hours and then cooled naturally to obtain a honeycomb activated carbon catalyst with a diameter of ~5mm and a length of ~5mm.

[0051] Example 2

[0052] Select activated carbon powder with a 200 mesh pass rate of more than 90% and a moisture content of less than 10% (iodine value 1500m 2 / g) as raw materials, attapulgite clay and kaolin (attapulgite clay: kaolin = 1:1) with a 200 mesh pass rate of more than 95% and a moisture content of less than 10% as inorganic binders, copper oxide with a 200 mesh pass rate of more than 95% and a moisture content of less than 10% as active components, activated carbon powder, inorganic binder, and active components are put into a stirring reaction tank equipped with 65°C hot water according to a mass ratio of 1:0.6:0.2 for hydrothermal reaction for 2 hours, and 5-20% dilute phosphoric acid is used to adjust the pH to 5-7 during the hydrothermal reaction to obtain a mixed slurry with a solid content of 15-30%. The mixed slurry is pumped to a dehydrator through a feed pump, and after the feed is full, it is dehydrated by 10-20MPa high-pressure extrusion, and the filtered water is reused to enter the stirring tank for uniform slurrying, and the material is discharged after dehydration to obtain a mixed mud material with a filter cake moisture content of less than 55%.

[0053] The mixed mud is conveyed to the kneading machine via a conveyor belt and kneaded for 45 minutes. The material is conveyed to the conveyor belt and conveyed to the cylindrical extruder for extrusion molding to obtain a crude columnar mud. The crude columnar mud is conveyed to the cylindrical extruder with a vacuum of -0.06 to -0.09 MPa via a conveyor belt for extrusion molding to obtain a refined columnar mud; the refined columnar mud is conveyed by a belt to the extruder equipped with a honeycomb mold for extrusion molding, and then automatically cut to obtain a honeycomb molding wet material; the honeycomb molding wet material is placed in a drying room via a conveyor belt or manually, and is dried in three temperature sections of 30 to 40°C, 40 to 50°C, and 50 to 80°C in sequence. The moisture content after drying is less than 5%, and a honeycomb dry material is obtained.

[0054] The honeycomb dry material is put into a 650℃ sealed oxygen-deficient high-temperature furnace for activation via a conveyor belt. The high-temperature furnace uses high-temperature gas from the full combustion of natural gas for heating. The activated flue gas is passed through a heat exchanger to obtain hot air for heating and drying. It is activated for 4 hours and then cooled naturally to obtain a honeycomb activated carbon catalyst with a diameter of ~5mm and a length of ~5mm.

[0055] Example 3

[0056] Select activated carbon powder with a 200 mesh pass rate of more than 90% and a moisture content of less than 10% (iodine value 1500m 2 / g) as raw materials, attapulgite clay and kaolin (attapulgite clay: kaolin = 1:1) with a 200 mesh pass rate of more than 95% and a moisture content of less than 10% as inorganic binders, copper oxide with a 200 mesh pass rate of more than 95% and a moisture content of less than 10% as active components, activated carbon powder, inorganic binder, and active components are put into a stirring reaction tank equipped with 65°C hot water according to a mass ratio of 1:0.8:0.2 for hydrothermal reaction for 2 hours, and 5-20% dilute phosphoric acid is used to adjust the pH to 5-7 during the hydrothermal reaction to obtain a mixed slurry with a solid content of 15-30%. The mixed slurry is pumped to a dehydrator through a feed pump, and after the feed is full, it is dehydrated by 10-20MPa high-pressure extrusion, and the filtered water is reused to enter the stirring tank for uniform slurrying, and the material is discharged after dehydration to obtain a mixed mud material with a filter cake moisture content of less than 55%.

[0057] The mixed mud is conveyed to the kneading machine via a conveyor belt and kneaded for 45 minutes. The material is conveyed to the conveyor belt and conveyed to the cylindrical extruder for extrusion molding to obtain a crude columnar mud. The crude columnar mud is conveyed to the cylindrical extruder with a vacuum of -0.06 to -0.09 MPa via a conveyor belt for extrusion molding to obtain a refined columnar mud; the refined columnar mud is conveyed by a belt to the extruder equipped with a honeycomb mold for extrusion molding, and then automatically cut to obtain a honeycomb molding wet material; the honeycomb molding wet material is placed in a drying room via a conveyor belt or manually, and is dried in three temperature sections of 30 to 40°C, 40 to 50°C, and 50 to 80°C in sequence. The moisture content after drying is less than 5%, and a honeycomb dry material is obtained.

[0058] The honeycomb dry material is put into a 650℃ sealed oxygen-deficient high-temperature furnace for activation via a conveyor belt. The high-temperature furnace uses high-temperature gas from the full combustion of natural gas for heating. The activated flue gas is passed through a heat exchanger to obtain hot air for heating and drying. It is activated for 4 hours and then cooled naturally to obtain a honeycomb activated carbon catalyst with a diameter of ~5mm and a length of ~5mm.

[0059] Example 4

[0060] Select activated carbon powder with a 200 mesh pass rate of more than 90% and a moisture content of less than 10% (iodine value 1500m 2 / g) as raw materials, attapulgite clay and kaolin (attapulgite clay: kaolin = 1:1) with a 200 mesh pass rate of more than 95% and a moisture content of less than 10% as inorganic binders, copper oxide with a 200 mesh pass rate of more than 95% and a moisture content of less than 10% as active components, activated carbon powder, inorganic binder, and active components are put into a stirring reaction tank equipped with 65°C hot water according to a mass ratio of 1:1:0.2 for hydrothermal reaction for 2 hours, and 5-20% dilute phosphoric acid is used to adjust the pH to 5-7 during the hydrothermal reaction to obtain a mixed slurry with a solid content of 15-30%. The mixed slurry is pumped to a dehydrator through a feed pump, and after the feed is full, it is dehydrated by 10-20MPa high-pressure extrusion, and the filtered water is reused to enter the stirring tank for uniform slurrying, and the material is discharged after dehydration to obtain a mixed mud material with a filter cake moisture content of less than 55%.

[0061] The mixed mud is conveyed to the kneading machine via a conveyor belt and kneaded for 45 minutes. The material is conveyed to the conveyor belt and conveyed to the cylindrical extruder for extrusion molding to obtain a crude columnar mud. The crude columnar mud is conveyed to the cylindrical extruder with a vacuum of -0.06 to -0.09 MPa via a conveyor belt for extrusion molding to obtain a refined columnar mud; the refined columnar mud is conveyed by a belt to the extruder equipped with a honeycomb mold for extrusion molding, and then automatically cut to obtain a honeycomb molding wet material; the honeycomb molding wet material is placed in a drying room via a conveyor belt or manually, and is dried in three temperature sections of 30 to 40°C, 40 to 50°C, and 50 to 80°C in sequence. The moisture content after drying is less than 5%, and a honeycomb dry material is obtained.

[0062] The honeycomb dry material is put into a 650℃ sealed oxygen-deficient high-temperature furnace for activation via a conveyor belt. The high-temperature furnace uses high-temperature gas from the full combustion of natural gas for heating. The activated flue gas is passed through a heat exchanger to obtain hot air for heating and drying. It is activated for 4 hours and then cooled naturally to obtain a honeycomb activated carbon catalyst with a diameter of ~5mm and a length of ~5mm.

[0063] Example 5

[0064] Select activated carbon powder with a 200 mesh pass rate of more than 90% and a moisture content of less than 10% (iodine value 1500m 2 / g) as raw materials, attapulgite clay, kaolin, and sepiolite powder (attapulgite clay: kaolin: sepiolite powder = 1:1:0.5) with a 200 mesh pass rate of more than 95% and a moisture content of less than 10% as inorganic binders, manganese oxide, cobalt oxide, and lanthanum oxide (manganese oxide: cobalt oxide: lanthanum oxide = 15:4:1) with a 200 mesh pass rate of more than 95% and a moisture content of less than 10% as active components, activated carbon powder, inorganic binder, and active components are put into a stirring reaction tank equipped with 75°C hot water in a mass ratio of 1:1:0.1 for hydrothermal reaction for 1.5 hours, 5-20% dilute phosphoric acid is used to adjust the pH to 5-7 during the hydrothermal reaction, and a mixed slurry with a solid content of 15-30% is obtained. The mixed slurry is pumped to the dewatering machine through the feed pump. After the feed is full, it is dehydrated by 10-20MPa high-pressure extrusion. The filtered water is recycled and sent to the mixing tank for uniform slurry mixing. After dehydration, the material is unloaded to obtain a mixed mud material with a moisture content of less than 55% in the filter cake.

[0065] The mixed mud is conveyed to the kneading machine via a conveyor belt and kneaded for 60 minutes. The material is conveyed to the conveyor belt and conveyed to the cylindrical extruder for extrusion molding to obtain a crude columnar mud. The crude columnar mud is conveyed to the cylindrical extruder with a vacuum of -0.06 to -0.09 MPa via a conveyor belt for extrusion molding to obtain a refined columnar mud; the refined columnar mud is conveyed by a belt to the extruder equipped with a honeycomb mold for extrusion molding, and then automatically cut to obtain a honeycomb molding wet material; the honeycomb molding wet material is placed in a drying room via a conveyor belt or manually, and is dried in three temperature sections of 30 to 40°C, 40 to 50°C, and 50 to 80°C in sequence. The moisture content after drying is less than 5%, and a honeycomb dry material is obtained.

[0066] The honeycomb dry material is put into a 750℃ sealed oxygen-deficient high-temperature furnace for activation via a conveyor belt. The high-temperature furnace uses high-temperature gas from the full combustion of natural gas for heating. The activated flue gas is passed through a heat exchanger to obtain hot air for heating and drying. The material is activated for 5 hours and then cooled naturally to obtain a honeycomb activated carbon catalyst with a diameter of ~5mm and a length of ~5mm.

[0067] Example 6

[0068] Select activated carbon powder with a 200 mesh pass rate of more than 90% and a moisture content of less than 10% (iodine value 1500m 2 / g) as raw materials, attapulgite clay, kaolin, and sepiolite powder (attapulgite clay: kaolin: sepiolite powder = 1:1:0.5) with a 200 mesh pass rate of more than 95% and a moisture content of less than 10% as inorganic binders, manganese oxide, cobalt oxide, and lanthanum oxide (manganese oxide: cobalt oxide: lanthanum oxide = 15:4:1) with a 200 mesh pass rate of more than 95% and a moisture content of less than 10% as active components, activated carbon powder, inorganic binder, and active components are put into a stirring reaction tank equipped with 75°C hot water in a mass ratio of 1:1:0.3 for hydrothermal reaction for 1.5 hours, 5-20% dilute phosphoric acid is used to adjust the pH to 5-7 during the hydrothermal reaction, and a mixed slurry with a solid content of 15-30% is obtained. The mixed slurry is pumped to the dewatering machine through the feed pump. After the feed is full, it is dehydrated by 10-20MPa high-pressure extrusion. The filtered water is recycled and sent to the mixing tank for uniform slurry mixing. After dehydration, the material is unloaded to obtain a mixed mud material with a moisture content of less than 55% in the filter cake.

[0069] The mixed mud is conveyed to the kneading machine via a conveyor belt and kneaded for 60 minutes. The material is conveyed to the conveyor belt and conveyed to the cylindrical extruder for extrusion molding to obtain a crude columnar mud. The crude columnar mud is conveyed to the cylindrical extruder with a vacuum of -0.06 to -0.09 MPa via a conveyor belt for extrusion molding to obtain a refined columnar mud; the refined columnar mud is conveyed by a belt to the extruder equipped with a honeycomb mold for extrusion molding, and then automatically cut to obtain a honeycomb molding wet material; the honeycomb molding wet material is placed in a drying room via a conveyor belt or manually, and is dried in three temperature sections of 30 to 40°C, 40 to 50°C, and 50 to 80°C in sequence. The moisture content after drying is less than 5%, and a honeycomb dry material is obtained.

[0070] The honeycomb dry material is put into a 750℃ sealed oxygen-deficient high-temperature furnace for activation via a conveyor belt. The high-temperature furnace uses high-temperature gas from the full combustion of natural gas for heating. The activated flue gas is passed through a heat exchanger to obtain hot air for heating and drying. The material is activated for 5 hours and then cooled naturally to obtain a honeycomb activated carbon catalyst with a diameter of ~5mm and a length of ~5mm.

[0071] Example 7

[0072] Select activated carbon powder with a 200 mesh pass rate of more than 90% and a moisture content of less than 10% (iodine value 1500m 2 / g) as raw materials, attapulgite clay, kaolin, and sepiolite powder (attapulgite clay: kaolin: sepiolite powder = 1:1:0.5) with a 200 mesh pass rate of more than 95% and a moisture content of less than 10% as inorganic binders, manganese oxide, cobalt oxide, and lanthanum oxide (manganese oxide: cobalt oxide: lanthanum oxide = 15:4:1) with a 200 mesh pass rate of more than 95% and a moisture content of less than 10% as active components, activated carbon powder, inorganic binder, and active components are put into a stirring reaction tank equipped with 75°C hot water in a mass ratio of 1:1:0.5 for hydrothermal reaction for 1.5 hours, 5-20% dilute phosphoric acid is used to adjust the pH to 5-7 during the hydrothermal reaction, and a mixed slurry with a solid content of 15-30% is obtained. The mixed slurry is pumped to the dewatering machine through the feed pump. After the feed is full, it is dehydrated by 10-20MPa high-pressure extrusion. The filtered water is recycled and sent to the mixing tank for uniform slurry mixing. After dehydration, the material is unloaded to obtain a mixed mud material with a moisture content of less than 55% in the filter cake.

[0073] The mixed mud is conveyed to the kneading machine via a conveyor belt and kneaded for 60 minutes. The material is conveyed to the conveyor belt and conveyed to the cylindrical extruder for extrusion molding to obtain a crude columnar mud. The crude columnar mud is conveyed to the cylindrical extruder with a vacuum of -0.06 to -0.09 MPa via a conveyor belt for extrusion molding to obtain a refined columnar mud; the refined columnar mud is conveyed by a belt to the extruder equipped with a honeycomb mold for extrusion molding, and then automatically cut to obtain a honeycomb molding wet material; the honeycomb molding wet material is placed in a drying room via a conveyor belt or manually, and is dried in three temperature sections of constant humidity conditions of 30 to 40°C, 40 to 50°C, and 50 to 80°C in sequence. The moisture content after drying is less than 5%, and a honeycomb dry material is obtained.

[0074] The honeycomb dry material is put into a 750℃ sealed oxygen-deficient high-temperature furnace for activation via a conveyor belt. The high-temperature furnace uses high-temperature gas from the full combustion of natural gas for heating. The activated flue gas is passed through a heat exchanger to obtain hot air for heating and drying. The material is activated for 5 hours and then cooled naturally to obtain a honeycomb activated carbon catalyst with a diameter of ~5mm and a length of ~5mm.

[0075] Example 8

[0076] Select activated carbon powder with a 200 mesh pass rate of more than 90% and a moisture content of less than 10% (iodine value 1500m 2 / g) as raw materials, attapulgite clay, kaolin, and sepiolite powder (attapulgite clay: kaolin: sepiolite powder = 1:1:0.5) with a 200 mesh pass rate of more than 95% and a moisture content of less than 10% as inorganic binders, manganese oxide, cobalt oxide, and lanthanum oxide (manganese oxide: cobalt oxide: lanthanum oxide = 15:4:1) with a 200 mesh pass rate of more than 95% and a moisture content of less than 10% as active components, activated carbon powder, inorganic binder, and active components are put into a stirring reaction tank equipped with 100°C hot water in a mass ratio of 1:1:0.4 for hydrothermal reaction for 0.5h, 5-20% dilute phosphoric acid is used to adjust the pH to 5-7 during the hydrothermal reaction, and a mixed slurry with a solid content of 15-30% is obtained. The mixed slurry is pumped to the dewatering machine through the feed pump. After the feed is full, it is dehydrated by 10-20MPa high-pressure extrusion. The filtered water is recycled and sent to the mixing tank for uniform slurry mixing. After dehydration, the material is unloaded to obtain a mixed mud material with a moisture content of less than 55% in the filter cake.

[0077] The mixed mud is conveyed to the kneading machine via a conveyor belt and kneaded for 30 minutes. The material is conveyed to the conveyor belt and conveyed to the cylindrical extruder for extrusion molding to obtain a crude columnar mud. The crude columnar mud is conveyed to the cylindrical extruder with vacuum at -0.06~-0.09MPa via a conveyor belt for extrusion molding to obtain a refined columnar mud; the refined columnar mud is conveyed by a belt to the extruder equipped with a honeycomb mold for extrusion molding, and then automatically cut to obtain a honeycomb molding wet material; the honeycomb molding wet material is placed in a drying room via a conveyor belt or manually, and is dried in three temperature sections of 30~40℃, 40~50℃, and 50~80℃ in sequence. The moisture content after drying is less than 5%, and a honeycomb dry material is obtained.

[0078] The honeycomb dry material is put into a 500℃ sealed oxygen-deficient high-temperature furnace for activation via a conveyor belt. The high-temperature furnace uses high-temperature gas from the full combustion of natural gas for heating. The activated flue gas is passed through a heat exchanger to obtain hot air for heating and drying. The material is activated for 8 hours and then cooled naturally to obtain a honeycomb activated carbon catalyst with a diameter of ~5mm and a length of ~5mm.

[0079] Example 9

[0080] Select activated carbon powder with a 200 mesh pass rate of more than 90% and a moisture content of less than 10% (iodine value 1500m 2 / g) as raw materials, attapulgite clay, kaolin, and sepiolite powder (attapulgite clay: kaolin: sepiolite powder = 1:1:0.5) with a 200 mesh pass rate of more than 95% and a moisture content of less than 10% as inorganic binders, manganese oxide, cobalt oxide, and lanthanum oxide (manganese oxide: cobalt oxide: lanthanum oxide = 15:4:1) with a 200 mesh pass rate of more than 95% and a moisture content of less than 10% as active components, activated carbon powder, inorganic binder, and active components are put into a stirring reaction tank equipped with 30°C hot water in a mass ratio of 1:1:0.4 for hydrothermal reaction for 3 hours, 5-20% dilute phosphoric acid is used to adjust the pH to 5-7 during the hydrothermal reaction, and a mixed slurry with a solid content of 15-30% is obtained. The mixed slurry is pumped to the dewatering machine through the feed pump. After the feed is full, it is dehydrated by 10-20MPa high-pressure extrusion. The filtered water is recycled and sent to the mixing tank for uniform slurry mixing. After dehydration, the material is unloaded to obtain a mixed mud material with a moisture content of less than 55% in the filter cake.

[0081] The mixed mud is conveyed to the kneading machine via a conveyor belt and kneaded for 50 minutes. The material is conveyed to the conveyor belt and conveyed to the cylindrical extruder for extrusion molding to obtain a crude columnar mud. The crude columnar mud is conveyed to the cylindrical extruder with a vacuum of -0.06 to -0.09 MPa via a conveyor belt for extrusion molding to obtain a refined columnar mud; the refined columnar mud is conveyed by a belt to the extruder equipped with a honeycomb mold for extrusion molding, and then automatically cut to obtain a honeycomb molding wet material; the honeycomb molding wet material is placed in a drying room via a conveyor belt or manually, and is dried in three temperature sections of 30 to 40°C, 40 to 50°C, and 50 to 80°C in sequence. The moisture content after drying is less than 5%, and a honeycomb dry material is obtained.

[0082] The honeycomb dry material is put into a sealed oxygen-deficient high-temperature furnace at 800℃ through a conveyor belt for activation. The high-temperature furnace uses high-temperature gas from the full combustion of natural gas for heating. The activated flue gas is passed through a heat exchanger to obtain hot air for heating and drying. It is activated for 4 hours and then cooled naturally to obtain a honeycomb activated carbon catalyst with a diameter of ~5mm and a length of ~5mm.

[0083] Comparative Example 1

[0084] The technical solution of this comparative example is basically the same as that of Example 1, except that the activated carbon powder and the inorganic binder are added in a mass ratio of 1:0.4.

[0085] Comparative Example 2

[0086] The technical solution of this comparative example is basically the same as that of Example 1, except that the activated carbon powder and the inorganic binder are added in a mass ratio of 1:0.2.

[0087] Comparative Example 3

[0088] The technical solution of this comparative example is basically the same as that of Example 1, except that the activated carbon powder and the inorganic binder are added in a mass ratio of 1:2.

[0089] Comparative Example 4

[0090] The technical solution of this comparative example is basically the same as that of Example 1, except that the activated carbon powder and the inorganic binder are added in a mass ratio of 1:3.

[0091] Comparative Example 5

[0092] The technical scheme of this comparative example is basically the same as that of Example 2, except that 5-20% dilute hydrochloric acid is used to adjust the pH to 5-7 during the hydrothermal reaction.

[0093] Comparative Example 6

[0094] The technical scheme of this comparative example is basically the same as that of Example 5, except that the activated carbon powder, the inorganic binder and the active component are added in a mass ratio of 1:1:0.6.

[0095] Comparative Example 7

[0096] The technical scheme of this comparative example is basically the same as that of Example 5, except that the activated carbon powder, the inorganic binder and the active component are added in a mass ratio of 1:1:0.9.

[0097] Comparative Example 8

[0098] The technical scheme of this comparative example is basically the same as that of Example 8, except that 5-20% dilute sulfuric acid is used to adjust the pH to 5-7 during the hydrothermal reaction.

[0099] Product performance testing

[0100] 1) The strength, adsorption performance and specific surface area of ​​Examples 1-4 and Comparative Examples 1-5 were tested respectively, and the test results are shown in Table 1 below:

[0101]

[0102] From the data of Examples 1-4 and Comparative Examples 1-4, it can be seen that with the increase of inorganic binder, the strength of the activated carbon catalyst gradually increases, but the adsorption performance gradually decreases. When the ratio of activated carbon powder to inorganic binder is greater than 1:0.5, the strength of the prepared granular activated carbon catalyst is significantly reduced, and when the ratio of activated carbon powder to inorganic binder is less than 1:1, the adsorption performance of activated carbon is significantly reduced; therefore, preferably activated carbon powder to inorganic binder = 1:0.5 to 1. Comparing the data of Example 2 with Comparative Example 5, it can be seen that the use of phosphoric acid in step 1) can further improve the strength and adsorption performance of the finished product.

[0103] 2) The strength, adsorption performance, specific surface area and catalytic performance of Examples 5-9 and Comparative Examples 6-8 were tested respectively, and the test results are shown in Table 2 below:

[0104] Catalytic performance test: The prepared catalyst was applied to the ozone oxidation wastewater process, using a bubbling bed reactor, and the wastewater COD was 635 mg / L. The reaction conditions were normal temperature and pressure, catalyst dosage 20 g / L, wastewater 500 mL, ozone flow rate 100 mL / min, reaction time 30 min, and the COD removal rate of the wastewater was recorded.

[0105]

[0106] From the data of Examples 5-8 and Comparative Examples 6-7, it can be seen that with the increase of active components, the strength of the activated carbon catalyst has no obvious change, the adsorption performance gradually decreases, and the catalytic performance of the activated carbon catalyst shows a trend of first rising and then falling. When the ratio of activated carbon powder to active component is 1:0.3-0.4, the catalytic performance of the activated carbon catalyst is optimal. Comparing the data of Example 2 with Comparative Example 5, it can be seen that the use of phosphoric acid can further improve the strength and adsorption performance of the finished product. Comparing the data of Example 8 with Comparative Example 8, it can be seen that the use of phosphoric acid in step 1) can further improve the adsorption performance and catalytic activity of the finished product.

[0107] The above embodiments further illustrate the purpose, technical solutions and advantages of the present invention. It should be understood that the above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

[0108] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for producing a multifunctional activated carbon catalyst, characterized in that: The following steps are involved: 1) Hydrothermal slurry preparation: The activated carbon powder, the inorganic binder and the active component are put into a stirring reaction tank equipped with hot water in a mass ratio of 1:0.5 to 1:0 to 0.5 for hydrothermal reaction, and the pH is adjusted to 5 to 7 with dilute phosphoric acid during the hydrothermal reaction to obtain a mixed slurry; wherein the content of the active component is not 0; the inorganic binder is selected from one or more of attapulgite clay, kaolin and sepiolite powder; 2) High pressure dehydration: The mixed slurry in step 1) is pumped to a dehydrator, and after the feed is full, it is dehydrated, and the material is unloaded after dehydration to obtain a mixed mud material with a filter cake moisture content of less than 55%; 3) Rough refining and molding: The mixed clay material of step 2) is conveyed to a kneader for kneading, and the discharged material is conveyed to a cylindrical extruder for extrusion molding to obtain a crude columnar clay material; 4) Refining and molding: The crude columnar clay material in step 3) is conveyed by a conveyor belt to a vacuum cylindrical extruder for extrusion molding to obtain a refined columnar clay material; 5) Mold forming: The refined columnar mud material of step 4) is conveyed to an extruder equipped with a honeycomb mold for extrusion molding, and then automatically cut to obtain a honeycomb molding wet material; 6) Heating and drying: The honeycomb forming wet material of step 5) is gradually dried at a temperature range of 30-80° C. to a moisture content of less than 5%, thereby obtaining a honeycomb dry material; 7) Activation: The honeycomb dry material in step 6) is put into a sealed oxygen-deficient high-temperature furnace at 500-800°C for activation, and a honeycomb activated carbon catalyst is obtained after cooling; the high-temperature furnace is heated by high-temperature gas from fully combusted natural gas.

2. The method for producing a multifunctional activated carbon catalyst according to claim 1, characterized in that: In step 1), the activated carbon powder has a 200-mesh pass rate of more than 90% and a moisture content of less than 10%; the inorganic binder has a 200-mesh pass rate of more than 95% and a moisture content of less than 10%; the active component has a 200-mesh pass rate of more than 95% and a moisture content of less than 10%.

3. The method for producing a multifunctional activated carbon catalyst according to claim 1, characterized in that: The active component is a metal oxide, and the metal oxide is selected from one or more of manganese oxide, iron oxide, copper oxide, aluminum oxide, lanthanum oxide, cerium oxide, molybdenum oxide, and cobalt oxide.

4. The method for producing a multifunctional activated carbon catalyst according to claim 1, characterized in that: In step 1), the hot water temperature is 30-100° C., the hydrothermal reaction time is 0.5-3 h, and the solid content of the obtained mixed slurry is 15-30%; the dilute phosphoric acid is 5-20% phosphoric acid.

5. The method for producing a multifunctional activated carbon catalyst according to claim 1, characterized in that: In step 2), dehydration is performed by high pressure extrusion at 10-20 MPa.

6. The method for producing a multifunctional activated carbon catalyst according to claim 1, characterized in that: The filtered water obtained by dehydration in step 2) is recycled and fed into the stirred reactor for uniform slurry preparation.

7. The method for producing a multifunctional activated carbon catalyst according to claim 1, characterized in that: In step 3), the kneading time of the mixed mud is 30 to 60 minutes.

8. The method for producing a multifunctional activated carbon catalyst according to claim 1, characterized in that: The vacuum degree of the vacuum pump in step 4) is -0.06~-0.09MPa.

9. The method for producing a multifunctional activated carbon catalyst according to claim 1, characterized in that: In step 6), the mixture is gradually dried in a constant humidity environment at a temperature range of 30-80°C to a moisture content of less than 5%, specifically: Drying is carried out in three temperature ranges of 30~40℃, 40~50℃ and 50~80℃ respectively until the moisture content is less than 5%. The relative humidity of the constant humidity environment is controlled at 40~50%.

10. The method for producing a multifunctional activated carbon catalyst according to claim 1, characterized in that: In step 7), the activation time is 4 to 8 hours; the activated flue gas is passed through a heat exchanger to obtain hot air for heating and drying.

Citation Information

Patent Citations

  • Preparation method of metal-loaded catalyst for removing ammonia nitrogen in water through moderate catalytic ozonation

    CN111036221A

  • An ozone oxidation catalyst, its preparation method, and an ozone catalytic oxidation device.

    CN111992204B

  • A highly efficient moisture-resistant ozone decomposition catalyst, its preparation method and application

    CN112473728B

  • Mesoporous manganese-based composite oxide, preparation method and application thereof

    CN112604693A

  • Denitration catalyst adopting modified active carbon as base material and preparation method of denitration catalyst

    CN106111124A